T. P. N. Against "Spebo medical" healthcare institution: Woman's right to continue with the procedure of biomedically assisted fertilization after the death of her husband - Rusić Nikola (Glasnik Advokatske komore Vojvodine)
The court competent to decide in the first instance in the case of T. P. N. against the Health Institution SPEBO MEDICAL made a decision that woman has the right to continue the procedure of biomedically assisted fertilization which she started together with her husband, who died during the procedure. In this way, the court indirectly took the position that posthumous fertilization is allowed according to the positive law of the Republic of Serbia. This decision was later confirmed by a second instance decision. In this presentation, we will try to present what the court had in mind when making this decision, what is the impact of this decision on other cases with a similar factual situation, as well as the questions that by the nature of things are opened by accepting the position on the permissibility of posthumous fertilization.